Postpandemic immunity debt of common cold in England: an interrupted time series study - Char Leung; Li Su (International Journal of Infectious Diseases)
This study investigates immunity debt in five common cold viruses (adenovirus, parainfluenza virus, human metapneumovirus, rhinovirus, and respiratory syncytial virus) in England using weekly positivity rate data from UKHSA. An interrupted time series analysis assessed post-NPI effects with sensitivity analyses conducted to account for potential structural changes in viral dynamics across years. Results indicate significant immunity debt for adenovirus, parainfluenza virus, and respiratory syncytial virus. These findings highlight the need for public health preparedness post-NPI removal, particularly for vulnerable groups, and emphasize challenges in predicting immunity debt for viruses with high serotype diversity.